A critical review on phase change material energy storage systems with cascaded configurations. (10th February 2021) - Christopher, S.; Parham, K.; Mosaffa, A.H.; Farid, M.M.; Ma, Zhenjun; Thakur, Amrit Kumar; Xu, Huijin; Saidur, R.
Abstract: This paper reviews cascaded or multiple phase change materials (PCMs) approach to provide a fundamental understanding of their thermal behaviors, the performance in terms of heat transfer uniformity, and the influence of input parameters and different geometrical containments on the performance of latent heat thermal energy storage (LHTES) systems. Furthermore, the performance enhancement of energy components through the implementation of cascaded techniques and cascaded arrangements of PCMs accompanied by other enhancement approaches is discussed. The influence of stage numbers affecting the performance of the cascaded LHTES unit is summarized and the range of recommended values for those parameters is provided. Our critical evaluation demonstrates that replacing single PCM by multiple PCMs shows the possibility of improving the performance of TES in terms of energy, exergy and entransy charging/discharging rate along with increased stored/retrieved energy and exergy efficiency. It is also shown that the cascaded LHTES systems opens the doors of opportunity for the seasonal energy sources and extracting the optimum amount of energy within the stipulated time through the proper arrangement of PCMs. Finally, the discussions are extended to the challenges of implementing the cascaded PCMs with some recommendations for future research in this direction.